PEMANFAATAN REACT NATIVE DAN FIREBASE UNTUK PEMBUATAN APLIKASI JUAL-BELI ITEM GAME ONLINE - Ratih Nurdiyani Sari; Novrina Novrina; Arya Rangga Kusuma (Jurnal Larik: Ladang Artikel Ilmu Komputer, 2022)
Rocket League is a multi-platform game developed and published by Psyonix, this game has a car-soccer theme, where the player or user will control a car to direct the ball towards the enemy's goal to win the match. Rocket League presents the Trade feature, which is a feature that provides access to make transactions between users to be able to exchange items with tradable status. However, this feature has several limitations, namely that users basically cannot see items owned by other users when they want to find the desired item to exchange in the game. By creating an application, it is hoped that it can help users to trade items in the Rocket League game that is being broadcast between users in the application. Application development begins with application implementation and testing, where applications are built using the React Native framework and then assisted by the Firebase Platform on the Backend, and Android Studio as an IDE platform. From the results of the tests that have been carried out, the application can run with a minimum test benchmark having a smartphone specification of 2GB Ram capacity with an Exynyos 7870 Cortex A-53 2013 processor.